2009
DOI: 10.1017/s0007114509990213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of orally administered sodium butyrate before or after weaning on growth and several indices of gastrointestinal biology of piglets

Abstract: Sodium butyrate (SB) provided orally favours body growth and maturation of the gastrointestinal tract (GIT) in milk-fed pigs. In weaned pigs, conflicting results have been obtained. Therefore, we hypothesised that the effects of SB (3 g/kg DM intake) depend on the period (before v. after weaning) of its oral administration. From the age of 5 d, thirty-two pigs, blocked in quadruplicates within litters, were assigned to one of four treatments: no SB (control), SB before (for 24 d), or after (for 11-12 d) weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 58 publications
8
74
1
2
Order By: Relevance
“…Butyrate decreases intestinal expression levels of TNFa, IL-1b and IL-6 in patients with Crohn's diseases (158) . In piglets aged 40 d, Le Gall et al (111) have observed a tendency to a reduced expression of IL-8, in agreement with the results of Gibson & Rosella (191) who have demonstrated that, in vitro, IL-8 secretion by colonic crypt cells is suppressed by butyrate.…”
Section: Mechanisms Of Action Of Butyrate In Physiological and Patholsupporting
confidence: 82%
“…Butyrate decreases intestinal expression levels of TNFa, IL-1b and IL-6 in patients with Crohn's diseases (158) . In piglets aged 40 d, Le Gall et al (111) have observed a tendency to a reduced expression of IL-8, in agreement with the results of Gibson & Rosella (191) who have demonstrated that, in vitro, IL-8 secretion by colonic crypt cells is suppressed by butyrate.…”
Section: Mechanisms Of Action Of Butyrate In Physiological and Patholsupporting
confidence: 82%
“…5 months) which ingested MF and starter diet from 3 days after birth, whereas the measurements for other studies were obtained in milk-fed (Guilloteau et al , 2010b or in weaned (Slusarczyk et al 2010) calves aged at least 2 months. In fact, it was demonstrated, in different species, that butyrate must be ingested immediately after birth, but the growth performances were observed later in life , 2010b, Le Gall et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were realized mainly in milk-fed calf (Guilloteau et al , 2010b or in piglet before weaning (Kotunia et al 2004, Mazzoni et al 2008, Le Gall et al 2009, and sometimes during (or after) weaning in calf (Gorka et al 2009, 2011 or in piglet (Gálfi & Boroki 1990, Wang et al 2005, Biagi et al 2007, Le Gall et al 2009). These substances were found to have widespread positive effects on digestive secretions (pancreas and small intestine), digestibility and feed efficiency, growth rate, adiposity through the modulation of cell proliferation, differentiation, and function in the GIT, especially mucosal epithelial cells, and on defence systems (barrier function, antimicrobial potency, and immune system) in healthy and sick animals (Pouillart 1998, Partanen & Mroz 1999, Gauthier 2002, Scheppach & Weiler 2004, Franco et al 2005, Mroz 2005, Manzanilla et al 2006, Mazzoni et al 2008, Le Gall et al 2009, 2010b. Moreover, sodium-butyrate (Na-butyrate) supplementation in milk formula (MF) and/or starter diet intake by neonatal calves had a beneficial effect on calf growth and nutrient utilization, modified the relative weight of the different parts of the forestomach, and produced larger rumen papillae length and width, suggesting an enhancement of the rumen (Gorka et al 2009, 2011, Slusarczyk et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sodium butyrate and Yucca schidigera have received considerable attention, but most of the studies examined their influence on growth performance and the structure, function, and microbiology of the digestive tract (10,12,14,16,19). The majority of research on Yucca schidigera has been focused on odour elimination in animal production (1).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have been conducted using formic, lactic, citric, and other acids (16,22). In the last few years, beneficial effects of short-chain fatty acids (SCFAs) were confirmed in pigs (12,16) and in laying hens (28). The results of several studies on rats (15) and pigs (22) have shown that reducing the gastrointestinal pH due to addition of organic acids to the diet increases calcium absorption and retention, which may be of great importance for bone metabolism.…”
Section: Introductionmentioning
confidence: 99%